Clinical characteristics and demographics figures of patients with age-related macular degeneration at a tertiary-level hospital in Denpasar, Bali - Bobby Kristianto; Ari Andayani; Anak Agung Mas Putrawati Triningrat; Ni Made Ari Suryathi; I Wayan Gede Jayanegara; I Gusti Ayu Ratna Suryaningrum (DiscoverSys Inc., 2021)
Introduction: Age-Related Macular Degeneration (AMD) is a macular disease that characteristically affects the loss of central vision of the elderly. Unlike the western world, Indonesia has a relatively undocumented AMD epidemiology due to a lack of scientific attention, as indicated by few AMD publications. As a result, it is difficult to determine AMD's features and characteristics in the Indonesian population. This study aimed to evaluate AMD patients' characteristics and demographics at a tertiary hospital in Bali.Methods: This is a Cross-Sectional study. Data were collected from medical records on Sanglah General Hospital from January 2017 until December 2019. The characteristics and features were collected and analyzed. The characteristics and demo-figure were analyzed with descriptive statistics and a Chi-square test.Results: This study data consist of 172 patients, 90 (52.33 %) male and 82 (47.67 %) female. Most of the patients in the age group 66-83 years. The distribution of dry AMD showed the highest number on males, but the inverse occurs in wet AMD. Subjects had a smoking lifestyle in 50% of the patients. The smoking history more likely in dry AMD, but the inverse occurs in wet AMD. Hypertension occurs in more than half (51.16 %), with larger distribution in wet AMD. The proportion of gender, smoking history, hypertension but not age are significantly different between wet and dry AMD.Conclusion: Age-related macular degeneration is a common cause of blindness in the elderly population. This study found that the prevalence of AMD increases with age. The significant factors associated with AMD were sex, hypertension and smoking habit.